2007
DOI: 10.1364/oe.15.017509
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of SRS beam cleanup in graded-index fibers and the absence of SRS beam cleanup in step-index fibers

Abstract: We report using a Raman fiber laser (RFL) based on a multimode graded-index fiber as a novel method for beam combination of two continuous wave pump beams. Due to stimulated Raman scattering, the RFL generates a Stokes beam which can be up to 300% brighter than the pump beams. Up to 5.8 W of Stokes power is generated with an optical conversion efficiency of 56%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(58 citation statements)
references
References 11 publications
1
57
0
Order By: Relevance
“…Strikingly, we observed that the entire spectrum accessible to our instruments exhibits a remarkably robust and spatially coherent nonlinear modal profile, in spite of the initially highly multimode excitation [7]. This unexpected Kerr-induced beam self-organization towards a quasi-Gaussian shape is fundamentally different from the spatial beam cleanup of the Stokes wave based on Raman or Brillouin scattering, which was previously reported in the literature [9,10]. Fig.2.…”
Section: Resultssupporting
confidence: 47%
“…Strikingly, we observed that the entire spectrum accessible to our instruments exhibits a remarkably robust and spatially coherent nonlinear modal profile, in spite of the initially highly multimode excitation [7]. This unexpected Kerr-induced beam self-organization towards a quasi-Gaussian shape is fundamentally different from the spatial beam cleanup of the Stokes wave based on Raman or Brillouin scattering, which was previously reported in the literature [9,10]. Fig.2.…”
Section: Resultssupporting
confidence: 47%
“…Our experimental data show that the Kerr effect in a graded-index multimode fibre is the driving mechanism for overcoming speckle distortions, leading to a somewhat counter-intuitive effect resulting in a spatially clean output beam robust against fibre bending. Our observations demonstrate that nonlinear beam reshaping into the fundamental mode of a multimode fibre can be achieved even in the absence of a dissipative process such as stimulated scattering (Raman or Brillouin) [14,15].Beam propagation in multimode fibres (MMFs) is subject to a complex interplay of spatio-temporal processes. However, only few studies addressed nonlinear pulse propagation in MMFs, leaving this field largely untapped for the past thirty years.…”
mentioning
confidence: 86%
“…While it is well-known that SRS can improve the beam quality in GRIN-MM fibers [19], other multimode fiber structures such as double-clad fibers can be more effective in this regard and even produce single-mode output [20]. We therefore designed and fabricated a double-clad Raman gain fiber (DCRF) and evaluated it in a similar experimental setup.…”
Section: Double-clad Raman Gain Fibermentioning
confidence: 99%